Literacy probe, 7-9 : teacher's handbook - Bentley, Diana; Reid, Dee. (London : Hodder and Stoughton, 1999)
This book provides diagnostic tests focused on the basic literacy skills of struggling readers - children who are underperforming by two years or more - at two key points. The tests are designed to give a clear profile of the vital literacy skills the child has already acquired, and to pinpoint those skills needing to be addressed.
Keywords: Education; Teaching; Literacy; Literacy -- Study and teaching (Elementary)